CT imaging of acute pulmonary embolism - Henzler, Thomas; Barraza, J. Michael; Nance, John W.; Costello, Philip; Kriššák, Radko; Fink, Christian; Schoepf, U. Joseph (Journal of cardiovascular computed tomography, 2011)
CT pulmonary angiography (CTPA) has become the de facto clinical “gold standard” for the diagnosis of acute pulmonary embolism (PE) and has replaced catheter pulmonary angiography and ventilation-perfusion scintigraphy as the first-line imaging method. The factors underlying this algorithmic change are rooted in the high-sensitivity and specificity, cost-effectiveness, and 24-hour availability of CTPA. In addition, CTPA is superior to other imaging methods in its ability to diagnose and exclude, in a single examination, a variety of diseases that mimic the symptoms of PE. This article reviews the current role of CTPA in the diagnosis of acute PE as well as more recent developments, such as the use of CT parameters of right ventricular dysfunction for patient prognostication and the assessment of lung perfusion with CT.